1975
DOI: 10.1063/1.861168
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear breakup of a laminar liquid jet

Abstract: A perturbation analysis of the capillary instability of an inviscid liquid jet of circular cross section was carried out to third order. The results show that the nonlinear terms are responsible for the presence of satellite drops. The dimensionless cutoff wavenumber, which separates regions of stability and instability, remains unity to third order. The present theory was used in a computer simulation of jet breakup, and it was found that predicted surface wave profiles, disturbance amplification rates and dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(69 citation statements)
references
References 10 publications
3
66
0
Order By: Relevance
“…This observation is considered today as the first prediction of the formation of satellite drops. Good agreement of the predictions of his model with experimental results was found for the deviation of the jet surface shape from the single sinusoidal one [9], the satellite drop size [10,11] and the growth rate of the two first nonlinear harmonics for wave numbers less than the fastest growing mode [12]. For larger wave numbers (more precisely, greater than the fastest growing mode), Yuen's model does not predict the formation of satellite drops, even though they are still observed in the experiment [10].…”
supporting
confidence: 58%
“…This observation is considered today as the first prediction of the formation of satellite drops. Good agreement of the predictions of his model with experimental results was found for the deviation of the jet surface shape from the single sinusoidal one [9], the satellite drop size [10,11] and the growth rate of the two first nonlinear harmonics for wave numbers less than the fastest growing mode [12]. For larger wave numbers (more precisely, greater than the fastest growing mode), Yuen's model does not predict the formation of satellite drops, even though they are still observed in the experiment [10].…”
supporting
confidence: 58%
“…The problem was first studied experimentally by Plateau [24] and later theoretically by Lord Rayleigh [25], and is currently referred to as Rayleigh-Plateau (RP) instability. The RP instability has been extensively studied experimentally, theoretically, and numerically [24][25][26][27]. Moreover, the problem is fully axisymmetric and therefore suitable for the validation of our multiphase axisymmetric LBM model.…”
Section: Rayleigh-plateau (Rp) Instabilitymentioning
confidence: 99%
“…It may be noted that Rayleigh's original analysis predicts only the onset of breakup and not the formation of satellite droplets. To predict analytically satellite droplet formation, it has been shown that at least a third-order perturbation analysis of the Navier-Stokes equations (NSE) is needed [36]. Computations based on direct solutions of the NSE also predict the formation of the satellite droplets.…”
Section: Resultsmentioning
confidence: 99%